Kearifan Lokal Masyarakat Dalam Melestarikan Tradisi Pernikahan Pepadun di Lampung Utara - Roy Kembar Habibi; Eny Kusdarini (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
The purpose of writing this article is to find out the traditional marriage culture of pepadun in North Lampung as a legacy from the ancestors of pepadun. Therefore there is a need for cultural preservation that makes the hallmark of pepadun traditional marriages in North Lampung. This article was compiled using the library research method, which is a method of data collection which is carried out by utilizing sources and library materials. The results obtained were the culture of pepadun marriage in North Lampung, the cultural heritage of the people of North Lampung, which had existed since the early traditional wedding ceremonies. In the wedding there is a meeting of the bride and groom's family, a meeting of the indigenous tribes of pepadun, a procession of marriage in the wedding, and there is a release dance for the bride and groom, and there is a dance that will invite the bride and groom to dance in the evening. fund. The pepadun community has never let go of the culture of marriage that had been passed down by previous ancestors. The conclusion of this research is the culture of customary marriage of pepadun into a marriage culture that cannot be abandoned by the pepadun community, especially in North Lampung.